PENGARUH JUMLAH SALURAN MASUK TERHADAP KETANGGUHAN, KEKERASAN, DAN STRUKTUR MIKRO PADA PENGECORAN PULLEY DARI BESI COR DENGAN CETAKAN PASIR - Amfrudin, Muhammad (Jurnal Nosel, 2014)
The objectives of this research are to investigate: (1) the effect of the number of inlets on the toughness in the pulley; (2) the effect of the number of inlets on the toughness in the casting of pulley from gray cast iron; (2) the effect of the number of inlets on the hardness in the casting of pulley from gray cast iron; and (3) the effect of the number of inlets on the micro structure in the casting of pulley from cast iron and sand mold. This research was conducted in the Engineering Material Laboratory of Diploma Program of Vocational School, Gadjah Mada University. Three types of number of inlet were used in the casting of pulley from gray cast iron, namely: one-inlet type, two-inlet type, and three-inlet type by using wheel (ring) gate in the casting inlet system. The parameter of input in the data analysis consisted of the tests on toughness, hardness, and micro structure. The data of this research were analyzed by using the descriptive data analysis in which the results of the experiment were observed directly and analyzed and then the conclusion of this research was drawn. The results of this research are as follows: (1) the toughness of pulley with one-inlet type is higher due to slow congealment in such a way that more ferrite is collected; (2) ferrite has soft and ductile characteristics; (3) the hardness of pulley with three-inlet type is 205.8 VHN which is higher than that of pulley with two-inlet type (201.8 VHN) and that of pulley with one-inlet type (196.8 VHN); (4) the hardness of pulley with three-inlet type is higher due to quicker congealment in such a way that the perlite formed is spread more evenly and the amount of graphite formed is getting smaller; (4) perlite has hard and brittle characteristics. The microstructure of pulley specimen in this research is hard and strong perlite matrix. The structure of graphite and ferrite in the pulley specimen with one-inlet type is greater in amount than that in the pulley specimen with two-inlet type and that in the pulley specimen with three-inlet type. On the basis of the results of the research, a conclusion is drawn that the value of toughness of pulley with one-inlet type is 0.055 J/mm2 which is greater than that of toughness of pulley with two-inlet type (0.053 J/mm2) and that of toughness of pulley with three-inlet type (0.052 J/mm2).